(untitled) (Annals of Medical Research, 2024)
Aim: Asthma is one of the most commonly reported occupational lung diseases. Studies indicate that one of the primary causes of occupational asthma is baker’s asthma. This study aims to determine the prevalence of asthma and asthma-related symptoms among bakery workers in Malatya, Turkey. Materials and Methods: Designed as a cross-sectional study, this research was conducted through a survey to assess the prevalence of asthma, the frequency of asthma symptoms, and factors influencing asthma among bakery workers in Malatya between December 2022 and May 2023. Results: The study included 142 participants, comprising 139 men and 3 women. Of the participants, 35.5% had been working for over 21 years, while 34% had been employed for less than 10 years. Approximately 20% of participants reported atopic complaints. While 6.3% of workers were previously diagnosed with asthma, 14.1% had at least two asthma-related symptoms. The risk of asthma was notably higher among workers in dough production compared to those in other departments. Conclusion: Occupational exposure appears to significantly contribute to the increased frequency of asthma among bakers working in dough production.